Accurate Measurement of the Optical Constants n and k for a Series of 57 Inorganic and Organic Liquids for Optical Modeling and Detection - Myers, Tanya L; Tonkyn, Russell G; Danby, Tyler O; Taubman, Matthew S; Bernacki, Bruce E; Birnbaum, Jerome C; Sharpe, Steven W; Johnson, Timothy J (Applied spectroscopy, 2018)
For optical modeling and other purposes, we have created a library of 57 liquids for which we have measured the complex optical constants n and k. These liquids vary in their nature, ranging in properties that include chemical structure, optical band strength, volatility, and viscosity. By obtaining the optical constants, one can model most optical phenomena in media and at interfaces including reflection, refraction, and dispersion. Based on the works of others, we have developed improved protocols using multiple path lengths to determine the optical constants n/k for dozens of liquids, including inorganic, organic, and organophosphorus compounds. Detailed descriptions of the measurement and data reduction protocols are discussed; agreement of the derived optical constant n and k values with literature values are presented. We also present results using the n/k values as applied to an optical modeling scenario whereby the derived data are presented and tested for models of 1 µm and 100 µm layers for dimethyl methylphosphonate (DMMP) on both metal (aluminum) and dielectric (soda lime glass) substrates to show substantial differences between the reflected signal from highly reflective substrates and less-reflective substrates.